2015
DOI: 10.1016/j.jallcom.2015.03.101
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure, thermodynamics, magnetics and disorder properties of Be–Fe–Al intermetallics

Abstract: The elastic and magnetic properties, thermodynamical stability, deviation from stoichiometry and order/disorder transformations of phases that are relevant to Be alloys were investigated using density functional theory simulations coupled with phonon density of states calculations to capture temperature effects. A novel structure and composition were identified for the Be-Fe binary ε phase. In absence of Al, FeBe 5 is predicted to form at equilibrium above ∼1100 K, while the ε phase is stable only below ∼1500 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…Zero-point energy and temperature contributions to the Helmholtz free energy were obtained by integrating the phonon DOS, following the harmonic and quasi-harmonic approximations, as outlined in Burr et al (2015). Fig.…”
Section: Figurementioning
confidence: 99%
“…Zero-point energy and temperature contributions to the Helmholtz free energy were obtained by integrating the phonon DOS, following the harmonic and quasi-harmonic approximations, as outlined in Burr et al (2015). Fig.…”
Section: Figurementioning
confidence: 99%
“…As discussed in previous work [4], Fe is soluble in Be metal (i.e. a small negative solution energy), but also forms (more favourably) three intermetallic phases: ε-Fe 2+x Be 17−x , δ-FeBe 5 and ζ-FeBe 2 , with the latter two commonly observed in commercial alloys.…”
Section: Iron and Aluminiummentioning
confidence: 66%
“…In our previous work [4], we showed that lattice disorder plays an important role for AlFeBe 4 and -at high temperatures -for FeBe 5 . Calculating the energy associated with point defects within disordered phases is computationally impractical, hence the current work assumed only the ordered form of AlFeBe 4 and FeBe 5 .…”
Section: Computational Methodologymentioning
confidence: 87%
See 1 more Smart Citation
“…[3][4][5] More recently, efforts have been undertaken to evaluate its performance under fusion conditions both experimentally [6][7][8] and through modelling, whereby the fundamental defect processes, such as the interaction of interstitials, vacancies, impurities, and radiogenic H and He, have been characterized. [9][10][11][12] One issue that modelling has yet to investigate is the threshold displacement energy (E D ) of Be, which is a parameter used in estimations of how many point defects will be created during irradiation. This value may be fed into stochastic Monte-Carlo simulations and approaches based on derivatives of the Kinchin-Pease model, to evaluate the longterm irradiation response of materials.…”
Section: Introductionmentioning
confidence: 99%